LC-UV and LC-MS evaluation of stress degradation behaviour of tenatoprazole - Mahadik, Mahadeo V.; Bhusari, Vidhya K.; Kulkarni, Mahesh J.; Dhaneshwar, Sunil R. (Journal of Pharmaceutical and Biomedical Analysis, 2009)
In the present study, comprehensive stress testing of tenatoprazole was carried out according to ICH guideline Q1A (R2). Tenatoprazole was subjected to stress conditions of hydrolysis, oxidation, photolysis and neutral decomposition. Additionally, the solid drug was subjected to 50 degrees C for 60 days in dry-bath, and to the combined effect of temperature and humidity at 40 degrees C/75% RH. Extensive degradation was found to occur in acidic, neutral and oxidative conditions. Mild degradation was observed in basic conditions. The drug is relatively stable in the solid-state. The products formed under different stress conditions were investigated by LC and LC-MS. Successful separation of drug from degradation products formed under stress conditions was achieved on a Chemito ODS-3 column [C(18) (5 mu m, 250 mm x 4.6 mm, i.d.)] using methanol: 0.01 M acetate buffer pH 4.5 adjusted with glacial acetic acid (55:45) as the mobile phase at flow rate of 1 mL/min and the peak was detected using a UV detector set at 306 nm. The LC-MS m/z values and fragmentation patterns of degradation products formed under different stress conditions were studied and characterized through LC-MS fragmentation. Based on the results, degradation pathway for drug has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: HPLC; Stability-indicating method; Stress studies; Tenatoprazole; Validation